Competence and Motivation as Factors to Improve Performance of Employees in the Health Services of the Province of Health Department of DKI Jakarta - Yulius, Yopi (Journal of Law, Politic and Humanities, 2021)
The purpose of this study was to determine and analyze the influence of competence and work motivation on employee performance in the Health Service Sector (YANKES) of the West Java Provincial Health Office, either simultaneously or partially. The research method used in this research is a descriptive survey and an explanatory survey, the unit of analysis in this study is the employees in the Health Service Sector (YANKES) of the West Java Provincial Health Office with a sample of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that competence and work motivation simultaneously affect employee performance in the Health Service Sector (YANKES) of the West Java Provincial Health Office. However, partially dominant competence affects employee performance rather than work motivation. Because competence is more dominant in influencing performance, it becomes the first priority in improving employee performance. the Health Service Sector (YANKES) of the West Java Provincial Health Office is expected to improve the competence of employees in the Health Service Sector (YANKES) of the West Java Provincial Health Office by including training and education, so that they are able to work more professionally.